DELAYING MOTHERHOOD: UNRAVELING THE COMPLEX LINK BETWEEN REPRODUCTIVE TIMING AND ENDOMETRIOSIS RISK" A COMPREHENSIVE LITERATURE REVIEW WITH IN-CALL DEPTH HORMONAL AND METHODOLOGICAL ANALYSIS - Dr Amber Shams; Dr Phou Vitharith; Dr Samar Amin; Zareena Begum (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
**Background** Endometriosis remains is an estrogen dependent disorder occurring in approximately 10 % of reproductive age women arises with chronic pelvic pain dysmenorrhea infertility women. There is a recent demographic pattern of delayed childbearing age which increases the likelihood of prolonged unopposed estrogen exposure due to high chances of endometriosis. **Objective** Conduct a systematic review analyzing epidemiological and mechanistic factors exploring the association between delayed childbearing and heightened endometriosis risk with special emphasis on hormonal changes and methodological concerns such as reverse causation. **Methods** A systematic literature search was done on PubMed, Scopus, and Web of Science using including “endometriosis,” “delayed childbearing,” “nulliparity”, “exposure to estrogen,” and “reproductive aging.” Included were peer reviewed articles, systematic reviews, meta analyses, and epidemiology of the research published in English. **Results** We recorded the systematic study design data including population characteristics, hormonal mechanisms, and possible confounding factors. Observational studies have shown consistently that women who delay their first pregnancy or remain nulliparous tend to have a higher incidence of endometriosis. In the case of women temporally delaying conception, the definitive hormonal protective milieu of pregnancy featuring cyclic estrogen suppression with high progesterone is absent. Instead, there is likely transient prolonged estrogen exposure which may facilitate endometrial proliferation, angiogenesis, and inflammation. Nonetheless, considerable methodological issues, for instance, diagnostic heterogeneity and reverse causation where endometriosis literally procures infertility, muddles causal interpretation. The majority of the connections discussed in the previous sections are obscured by some level of confounding factors, and so are the endometriosis. **Conclusion** The defended association between delaying childbearing and increased risk for endometriosis is justified by both epidemiological as well as biological reasoning, though the interaction of reverse causation with confounding factors is highly complicated and requires prospective research with stringent standardized diagnostic protocols coupled with extensive biomarker evaluation. Resolving these matters becomes essential towards effective clinical guidance and favorable preventive methods.